To Remember or to Forget: The Role of Good and Bad Memories in Adoptive T Cell Therapy for Tumors - Mondino, Anna; Manzo, Teresa (Frontiers in Immunology, 2020)
The generation of immunological memory is a hallmark of adaptive immunity by which the immune system ‘remembers’ a previous encounter with an antigen expressed by pathogens, tumors, or normal tissues; and, upon secondary encounters, mounts faster and more effective recall responses. The establishment of T cell memory is influenced by both cell-intrinsic and extrinsic factors, including genetic, epigenetic and environmental triggers. Our current knowledge of the mechanisms involved in memory T cell differentiation has instructed new opportunities to engineer T cells with enhanced anti-tumor activity. The development of adoptive T cell therapy has emerged as a powerful approach to cure a subset of patients with advanced cancers. Efficacy of this approach often requires long-term persistence of transferred T cell products, which can vary according to their origin and manufacturing conditions. Host preconditioning and post-transfer supporting strategies have shown to promote their engraftment and survival by limiting the competition with a hostile tumor microenvironment and between pre-existing immune cell subsets. While in the general view pre-existing memory can confer a selective advantage to adoptive T cell therapy, here we propose that also “bad memories” -in the form of antigen-experienced T cell subsets- co-evolve with consequences on newly transferred lymphocytes. In this review, we will first provide an overview of selected features of memory T cell subsets and, then, discuss their putative implications for adoptive T cell therapy.